Internet of things : novel advances and envisioned applications - Acharjya, D. P., 1969-; Geetha, M. Kalaiselvi (Springer, 2017)
This book focuses on a combination of theoretical advances in the Internet of Things, cloud computing and its real-life applications to serve society. The book discusses technological innovations, authentication, mobility support and security, group rekeying schemes and a range of concrete applications. The Internet has restructured not only global interrelations, but also an unbelievable number of personal characteristics. Machines are increasingly able to control innumerable autonomous gadgets via the Internet, creating the Internet of Things, which facilitates intelligent communication between humans and things, and among things. The Internet of Things is an active area of current research, and technological advances have been supported by real-life applications to establish their soundness. The material in this book includes concepts, figures, graphs, and tables to guide researchers through the Internet of Things and its applications for society.
Keywords: Internet of things.; elektronické knihy; electronic books